Antipsychotic Prescriptions for Children Aged 5 Years or Younger: Do We Need Policy Oversight Standards?. (23rd October 2014) - Lòpez-De Fede, Ana; Vyavaharkar, Medha; Bellinger, Jessica D.
The use of antipsychotics in very young children is of concern given the lack of empirical evidence in their efficacy and long-term impact on children's health. This study examined the prescription of antipsychotics among children aged ≤5 years enrolled in a state Medicaid program. Secondary data analysis was conducted using the Medicaid administrative data of a southeastern state. Using SAS 9.3, descriptive statistics were performed to examine socio-demographic characteristics, psychiatric diagnoses, off-label use, receipt of medications from multiple psychotropic drug classes, and receipt of non-pharmacologic psychiatric services among children aged ≤5 years who received antipsychotic prescriptions in calendar year (CY) 2011. A total of 112 children in the target age group received antipsychotics in CY 2011, the most common prescription being risperidone. The most common listed psychiatric diagnosis was attention deficit hyperactivity disorder. Two in five children received antipsychotics for off-label use. Three in four children also received medications from at least one other psychotropic drug class. More than half did not receive adjunct psychiatric services. State-level policies offering specific guidance and recommendations for antipsychotic use among very young children are urgently needed. Future research is warranted to examine long-term impact of such practices on children's growth and development.